Prevalence of HIV at the Kokoyo informal gold mining site: what lies behind the glitter of gold with regard to HIV epidemics in Mali? A community-based approach (the ANRS-12339 Sanu Gundo cross-sectional survey). Issue 8 (3rd August 2017) - Sagaon-Teyssier, Luis; Balique, Hubert; Diallo, Fodié; Kalampalikis, Nikos; Mora, Marion; Bourrelly, Michel; Suzan-Monti, Marie; Spire, Bruno; Dembélé Keita, Bintou
Abstract : Objectives: The aim of this article was to estimate HIV prevalence and the factors associated with HIV seropositivity in the population living and working at the informal artisanal small-scale gold mining (IASGM) site of Kokoyo in Mali, using data from the Sanu Gundo survey. Our main hypothesis was that HIV prevalence is higher in the context of IASGM than in the country as a whole. Design: The ANRS-12339 Sanu Gundo was a cross-sectional survey conducted in December 2015. The quantitative survey consisted of face-to-face administration of questionnaires. Five focus groups were conducted for the qualitative survey. HIV prevalence was calculated for the sample, and according to the type of activity performed in IASGM. Settings: The IASGM site of Kokoyo, one of the largest sites in Mali (between 6000 and 1000 people). Participants: 224 respondents: 37.5% were gold-diggers, 33% retail traders, 6.7% tombolomas (ie, traditional guards) and 9% female sex workers. The remaining 13.8% reported another activity (mainly street vending). Primary and secondary outcome measures: HIV prevalence and HIV prevalence according to subgroup, as defined by their activity at the Kokoyo IASGM. A probit logistic regression was implemented to estimate the characteristics associated with HIV seropositivity. Results: HIV prevalence for the total sample was 8% (95% CI 7.7% to 8.3%), which is much higher than the 2015 national prevalence of 1.3%Joint United Nations Programme on HIV/AIDS (UNAIDS). The probability of HIV seropositivity was 7.8% (p=0.037) higher for female non-sex workers than for any other category, and this probability increased significantly with age. Qualitative data revealed the non-systematic use of condoms with sex workers; and long distance from health services was the main barrier to accessing care. Conclusions: Integrated policymaking should pay special attention to infectious diseases among populations in IASGM zones. Bringing information/prevention activities closer to people working in gold mining zones is an urgent public health action.